Perspectivas de los actores educativos del nuevo modelo de gestión en el sistema de educación intercultural bilingüe del Distrito 17D10 Cayambe-Pedro Moncayo-educación - Masapanta Cobacango, María Laura (2018)
The objective of this article is to analyze the new process management model (NMGP) implemented in District 17D10 Cayambe-Pedro Moncayo, does it meet the expectations of intercultural bilingual education and respect the intercultural principles of education in the internal processes that it executes the district or the parameters of the NMG that come from the western thought have prevented respecting the culture of indigenous peoples and nationalities?. The methodology used was qualitative-quantitative; that is, that an information survey was made on: perceptions, opinions and experiences of educational actors in the NMGP applied to the Intercultural Bilingual Education System (SEIB). The results of this article show that in the deconcentrated entities of the District and Educational Circuit the SEIB disappears and the absence of strategic direction in the operation of the SEIB; and in the internal processes that the educational District executes, no action that integrates interculturality is visualized, nor have logics been used from the Andean cosmovision; rather, the processes have been standardized by responding to a single "colonial matrix", thus generating a weakening of our Educational System.